The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.3171/spi.2002.97.1.0040
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenetic protein—2 application by a poly(d,l-lactide)—coated interbody cage: in vivo results of a new carrier for growth factors

Abstract: Object. Growth factors such as bone morphogenetic protein—2 (BMP-2) have been proven to promote spine fusion and to overcome the disadvantages of an autologous bone graft. The optimum method to deliver such growth factors remains a matter of discussion. The purpose of this study was to determine the safety and efficacy of a new poly(d,l-lactide) (PDLLA) carrier system for BMP-2 and to compare this carrier system with a collagen spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 40 publications
(54 reference statements)
3
24
0
1
Order By: Relevance
“…32 Kandziora et al reported 0 of 8 solid fusions using tricortical iliac crest bone graft, 1 of 8 using Harm's titanium mesh cages, and 0 of 8 using titanium box cages in sheep cervical spines (C3-C4) after 12 weeks. 36 Similar results were reported from the same laboratory using absorbable polymercoated titanium cages, 33,37 and complete fusions could only be demonstrated with the use of growth factors. 37 This group also reported 0 of 8 solid fusions with tricortical iliac crest graft, 0 of 7 with an absorbable 70:30 poly(L-lactide:D,L-lactide) copolymer cage, and 6 of 8 with an absorbable polymer-calcium phosphatecomposite (PCC) cage all stabilized with titanium plates.…”
Section: Discussionsupporting
confidence: 85%
“…32 Kandziora et al reported 0 of 8 solid fusions using tricortical iliac crest bone graft, 1 of 8 using Harm's titanium mesh cages, and 0 of 8 using titanium box cages in sheep cervical spines (C3-C4) after 12 weeks. 36 Similar results were reported from the same laboratory using absorbable polymercoated titanium cages, 33,37 and complete fusions could only be demonstrated with the use of growth factors. 37 This group also reported 0 of 8 solid fusions with tricortical iliac crest graft, 0 of 7 with an absorbable 70:30 poly(L-lactide:D,L-lactide) copolymer cage, and 6 of 8 with an absorbable polymer-calcium phosphatecomposite (PCC) cage all stabilized with titanium plates.…”
Section: Discussionsupporting
confidence: 85%
“…A marked atrophy of the uterus has been used as evidence of the success of ovariectomy for estrogen directly affects uterine weight. 10 Indeed, ovariectomy resulted in a significant decrease in uterine weight. Ironically, 32KP did not exhibit any uterotrophic activity; this lack of uterotrophic activity could be beneficial in reducing the risk of diseases associated with E2 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…19 The Food and Drug Administration has approved the use of a type-I collagen sponge enhanced with rhBMP-2 in combination with a tapered, threaded fusion cage (LT-CAGE; Medtronic Sofamor Danek) for the treatment of lumbar degenerative disc disease. 20 Although less attention has been focused on the use of rhBMP-2 in anterior cervical spine fusions, both animal [21][22][23] and human 24 studies have shown favorable outcomes. The primary feature was the ability of rhBMP-2 to enhance significantly the rate of fusion without associated adverse effects.…”
mentioning
confidence: 99%